2017
DOI: 10.4103/ijccm.ijccm_186_17
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of serum myoglobin and creatine phosphokinase for development of acute kidney injury in traumatic rhabdomyolysis

Abstract: Introduction:Rhabdomyolysis (RM) is a condition where there is injury to striated muscle fibers causing release of myoglobin, creatine phosphokinase (CPK), and other intracellular contents into the circulation. High myoglobin levels cause acute kidney injury (AKI). Trauma is the most common cause of RM and development of complications related to the degree of myoglobin released. Currently, the degree of RM is assessed and treatment is instituted based on serum CPK. As myoglobin is the direct cause of AKI, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 14 publications
2
24
0
Order By: Relevance
“…We were unable to establish an association between myoglobinuria and AKI due to the lack of uniform testing for urinary myoglobin. However, several studies have demonstrated that serum myoglobin is a better predictor of AKI than serum CK . One study which compared CK, urine myoglobin and serum myoglobin noted that although all three markers significantly correlated with AKI, serum myoglobin had the best area under the receiver operating curve for predicting AKI .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were unable to establish an association between myoglobinuria and AKI due to the lack of uniform testing for urinary myoglobin. However, several studies have demonstrated that serum myoglobin is a better predictor of AKI than serum CK . One study which compared CK, urine myoglobin and serum myoglobin noted that although all three markers significantly correlated with AKI, serum myoglobin had the best area under the receiver operating curve for predicting AKI .…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have demonstrated that serum myoglobin is a better predictor of AKI than serum CK. [13][14][15][16] One study which compared CK, urine myoglobin and serum myoglobin noted that although all three markers significantly correlated with AKI, serum myoglobin had the best area under the receiver operating curve for predicting AKI. 16 Furthermore, a systematic review found insufficient evidence for using urine myoglobin to predict AKI, and serum and urine myoglobin results can be discrepant.…”
Section: Discussionmentioning
confidence: 99%
“…The study primary endpoint was AKI (any stage of the KDIGO classification) over the first admission week. The secondary endpoints were AKI stage 2 or 3 and the occurrence of severe rhabdomyolysis as defined by a peak of myoglobin higher than 5000 μg/L as stated in several studies [22,23] or a peak of CK higher than 5000 U/L as proposed in the statement on prevention and management of acute renal failure in the ICU" published in 2010 [24] over the first 7 days of admission.…”
Section: Study Endpointsmentioning
confidence: 99%
“…Studies have shown that serum CK higher than 16,000 U/L are more likely to be associated with renal failure [12][13][14]. Raju et al [15] concluded that myoglobin is more higher sensitive test than serum CPK in predicting impending renal failure. The graphic representation of serum myoglobin and CK ( Figure 1) demonstrates how myoglobin peaked before CK in our patient.…”
Section: Discussionmentioning
confidence: 99%